Free-standing carbon nanotubes as non-metal electrocatalyst for oxygen evolution reaction in water splitting - Ali, Abid; Akyuz, Duygu; Asghar, Muhammad Adeel; Koca, Atif; Keskin, Bahadir (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Oxygen evolution reaction (OER) has significant impact on the overall electrochemical water splitting. We introduce, for the first time, a facile approach towards the fabrication of versatile electrode composed of free-standing multiwalled carbon nanotubes (MWCNTs) as electrocatalyst for the water splitting reaction. Directly extracted MWCNTs as sheets from vertically grown arrays transferred over the glass substrate, are used without any post treatment as a working electrode for OER. Onset potential of 1.60 V was achieved for MWCNTs which is significantly reduced as compared to platinum based metal electrode (1.72 V) with excellent current density. No surface modification, metal-free nature, flexibility and low cost with excellent catalytic activity proved this material as a promising candidate for the replacement of metal based electrodes in electrochemical water splitting. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Carbon nanotube sheets; Electrode fabrication; Electrocatalyst; Oxygen evolution reaction; Water splitting; METAL-FREE ELECTROCATALYSTS; HYDROGEN-PRODUCTION; LOW-COST; REDUCTION; CATALYSTS; GRAPHENE; OXIDATION; NANOPARTICLES; ELECTROLYSIS; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels